48 Cluster-Randomised Trial of a Targeted Intervention to Promote Exercise Self-Efficacy and Reduce Bmi in Children at Risk of Obesity. (October 2012) - Glazebrook, C; Batty, M; Mullan, N; Sayal, K; Nathan, D; McWilliams, L; Hogarth, L; MacDonald, I; Smyth, A; Yang, M; Guo, B; Hollis, C
Abstract : Background and aims: Being physically active can help to reduce the risk of obesity in later life. This study aimed to evaluate the effectiveness of a targeted, school-based intervention (Steps to Active Kids - STAK) in improving exercise self-efficacy and reducing BMI in children. Method: STAK is a 12 week, activity programme including activity diary, street dance DVD, circuit training and, for children at or above the 91 st centile weight for height, motivational interviewing and goal setting. STAK was evaluated in a cluster-randomised trial in 24 schools. Children aged 9 to 11 were screened for overweight, low exercise self-efficacy or asthma. Twelve schools were randomised to receive the STAK intervention and 12 to control. BMI, waist circumference and exercise self-efficacy were assessed at baseline and post intervention (4 months). Results: Of the 2479 children screened, 1065 children (43%) met the study inclusion criteria. Parents of 424 (40%) children consented to their child's participation with 4 months follow-up data available for 392 (92%). The groups were well matched at baseline. After controlling for baseline values and time between testing, children in the intervention group had higher total self-efficacy at 4 month follow-up. In the group of children who were overweight at baseline (=>91 st centile), those in the STAK intervention group had smaller waist circumference and lower BMI at 4 month follow-up. Conclusion: Preliminary analysis suggests that a targeted activity intervention has benefits for children at risk of obesity. Future analyses will explore if benefits are sustained at 12 months follow-up.